Nutritional interventions for adolescents using information and communication technologies (ICTs): A systematic review. - Giselle Rhaisa do Amaral E Melo; Fernanda de Carvalho Silva Vargas; Carolina Martins Dos Santos Chagas; Natacha Toral (PLoS ONE)
A cost-effective and interactive way of promoting healthy nutrition behaviors among adolescents is using information and communication technologies (ICTs). We systematically reviewed studies to identify technologies and their main characteristics used for nutritional interventions for adolescents, as well as to evaluate their quality and effectiveness. Our full protocol is available on the PROSPERO website (#CRD42016035882). A search was conducted across five databases for articles describing nutritional interventions that used ICTs designed mainly for healthy adolescents. Randomized controlled trials, quasi-experimental and observational studies, and full and original papers, all of them published from 2005 to 2015, were included. Study quality was assessed by the Effective Public Health Practice Project Quality Assessment Tool. Our search yielded 559 titles and abstracts. Eleven studies met the inclusion criteria. Participants were recruited mostly from schools. Study follow-up ranged from two weeks to two years. Four interventions were based on the Social Cognitive Theory. Interventional strategies included computer games, programs, text messages, and interactive CD-ROMs. Nine studies used computer-mediated ICTs. Five studies focused on multiple behaviors simultaneously. Participants were exposed to interventions only once, daily, weekly, or according to a pre-determined number of lessons. Five studies had significant outcomes. Our quality assessment revealed three studies to be weak due to non-representativeness of their samples and usage of non-validated questionnaires. Besides the heterogeneity and poor quality of the analyzed studies, it can be suggested that long-term interventions for adolescents that make use of frequent exposure to technological resources, and that have a theoretical component aimed at a single health behavior change, tend to be more successful.